Pengaturan Tindak Pidana Aborsi Dalam KUHP dan UU No. 36 Tahun 2009 Tentang Kesehatan - Adi Suputra, Ida Bagus Made; Parwata, I Gusti Ngurah (Kertha Wicara : Journal Ilmu Hukum; Vol 9 No 12 (2020)DO - 10.24843/KW.2020.v09.i12.p08, 2020)
The purpose of this study is to provide knowledge about the regulation now and future abortion regulations in the context of Indonesian criminal law reform. In examining the problems in this research, normative legal research methods are used by reviewing the Criminal Code and the Health Law. The results of the analysis of this study indicate that the criminal act of abortion has been regulated in Indonesian positive law, but in this regulation there is a conflict of norms which results in inconsistency between law enforcement against abortion perpetrators according to the Criminal Code and Law No. Health Law, so it is necessary to reform Indonesian criminal law to achieve equality in law enforcement.  Keywords: Crime, Abortion, Criminal Law Reform. Keywords: Criminal Act, Abortion, Criminal Law Reform